BS36 Selective activation of primed vascular smooth muscle cells. (4th June 2021) - Lambert, Jordi; Oc, Sebnem
Abstract : Dysregulation of vascular smooth muscle cells (VSMCs) is a hallmark of vascular diseases including aneurysm and atherosclerosis. VSMCs in healthy vessels maintain a contractile and quiescent phenotype, but can be 'activated' and undergo phenotypic switching to a synthetic, proliferative state when under stress. Previously, we have shown that VSMC expansion after carotid ligation and in atherosclerotic lesions is oligoclonal, meaning activation is restricted to few VSMCs (Chappell et al., 2016, PMID: 27682618). Further to this, we identified a small population of Sca1+ VSMCs with reduced expression of contractile markers in healthy vasculature (Dobnikar et al., 2018, PMID: 30385745), which we hypothesize may have increased responsiveness. However, the mechanisms behind selective VSMC activation and the relevance of Sca1+ cells in disease are yet to be elucidated. To investigate VSMC activation dynamics, we used a murine carotid ligation injury model, which acutely induces VSMC proliferation. We conducted single-cell RNA-sequencing (scRNA-seq) 5 days after injury, corresponding with the onset of proliferation. Dimensionality reduction showed that injury resulted in a gradient of VSMC phenotypes from contractile to proliferative, with no evidence of a distinct response by a dedicated progenitor population. To characterise this gradual phenotypic change, we performed trajectory analysis, where cells are ordered in 'pseudotime' based on gene expression similarity. Trajectory inference identified two injury response paths of which only one was associated with the transition to active cell proliferation, alongside extracellular matrix organization, and cell adhesion. The second path was enriched for genes associated with protein refolding. Sca1+ cells mapped to the proliferation-associated path and positioned prior to cells expressing cell cycle markers in pseudotime, supporting the hypothesis that Sca1+ cells represent a primed stage. As VSMCs expand clonally in vitro as in vivo, we conducted functional analysis of SCA1+ VSMCs using an in vitro model of clonal proliferation. While proliferation was not restricted to SCA1+ cells, attachment and clonal expansion of SCA1+ cells was increased and temporally advanced compared to SCA1- VSMCs. As genes differentially expressed along the proliferation associated path were also associated with the GO terms of cytoskeletal regulation and migration, we explored functional differences of SCA1+ VSMCs via imaging flow cytometry of F-actin and ROCK1. SCA1+ VSMCs from healthy vessels had a marked reduction in both proteins, suggestive of a less contractile and more migratory phenotype, in line with the hypothesis that these cells are primed. These findings cannot be directly translated to human disease as a human SCA1 orthologue is unknown. Therefore, we conducted scRNA-seq of the healthy human aorta, with the aim of identifying an equivalent population. Single-cell profiling of the human aorta also revealed a gradient of VSMC phenotypes, and trajectory analysis indicated remarkably similar gene expression changes to those that occur in the mouse injury model. Our findings elucidate mechanisms underlying selective VSMC activation by characterizing the associated transcriptional signature and suggest that phenotypic switching is advanced in VSMCs that are 'primed' in a cell-intrinsic manner. Analysis of human scRNA-seq data indicates that this primed population is relevant in disease, and that functional testing of identified candidate drivers can enable targeted treatments of VSMC dysregulation in atherosclerosis. Conflict of Interest: none